The Status of Family Planning Methods among Married Women of Kavre District in Nepal - Bista, Sarita (Journal of Population and Development, 2020)
This study examines the information of family planning methods among currently married women of reproductive age group at Kavre District of Nepal. The main objective of the study is to find out the actual situation of family planning methods and the specific objective of the study are to identify the demographic determinants of currently use of family planning methods and to assess the reason for usage and non-usage of family planning methods in the study area. Moreover, this study also attempts to find out the actual sources of information of contraceptive devices in the study area. The study usages 200 respondents from the three words of Ugratara VDC of the Kavre District of Nepal The main occupation of the respondents are agriculture and services. Among currently married women, 91 percent of the respondents are found to be familiaPr with at least one family planning method. Likewise, the major source of contraceptive devices of the respondents is found family planning clinics in the study area. The central purpose for using family planning methods is found for limiting the births. There are positive relationships between use of family planning methods and demographic variables.